Urbanization impact on the supply-demand budget of ecosystem services: Decoupling analysis - Peng, Jian; Wang, Xiaoyu; Liu, Yanxu; Zhao, Yan; Xu, Zihan; Zhao, Mingyue; Qiu, Sijing; Wu, Jiansheng (Ecosystem services, 2020)
•Identifying the correlation of ecosystem services from both supply and demand sides.•Clustering ecosystem services supply and demand bundles.•Decoupling urbanization impact on ecosystem services supply-demand budget. Correlation of ecosystem services (ES) considering both the supply and demand sides remains unclear, and research on urbanization impact on the ES supply-demand budget is lacking. Taking the rapidly urbanizing Pearl River Delta (PRD) urban agglomeration of China as an example, eight ES supply, demand and the supply-demand budget of 374 watersheds were quantified using an expert-based matrix. The trade-offs and synergies of ES were then explored from both the supply and demand sides, with identifying the ecosystem service bundles (ESBs) of supply, demand, and the supply-demand budget separately. Through decoupling analysis, the urbanization impact on the ES supply-demand budget was explored. The results showed that ESs were well supplied in high-altitude areas in the PRD urban agglomeration, and that watersheds with insufficient ES supply were concentrated along the Pearl River where population density was high. It was also observed that there were significant synergistic relationships in the ES supply-demand budget. And the average decoupling index of the supply-demand budget for total ES and the three urbanization indicators increased from GDP to DN of nighttime light, and to Population density. It is an important way to identify the trade-offs and synergies between ES supply-demand budgets, and to explore the decoupling between the ES supply-demand budget and urbanization, in order to provide comprehensive decision-making support for ES management in rapidly urbanized areas.